Lexical Analysis in Content Management System Details - Fadziso, Takudzwa (Global Disclosure of Economics and Business, 2019)
In cognitive science, understanding language by humans starts with recognition. Without the phase, understanding languages become a very cumbersome task. The task of the lexical analyzer is to read the various input characters grouping them into lexemes and producing an output of a sequence of tokens. But before we discuss lexical analysis further, we should have an overview of this research. Lexical analysis is best described as tokenization that converts a sequence of characters (program) into tokens with identifiable meanings. This study aims to look at the various terms or words related to lexical structure, purpose, and how they are applied to get the required result. The lexical analysis offers researchers an idea of the structural aspect of computer language and its semantic content. The work also talks about the advantages and disadvantages of lexical analysis.